The Impact of Civic Education Learning on National and State Awareness in Elementary School Students - Yolantika, Refa (International Journal of Students Education, 2025)
This article aims to analyze the impact of Civic Education (PKn) learning on national and state awareness in Elementary School (SD) students. Civic Education has an important role in instilling basic values of nationality and nationalism, which are important foundations in shaping the character and identity of the nation. This study uses a literature study method by reviewing various previous studies, articles, journals, and relevant books related to PKn learning at the elementary school level. The results of this study indicate that PKn learning has a direct impact on increasing students' national and state awareness. Through PKn subjects, students are introduced to values such as the rights and obligations of citizens, the importance of maintaining national unity, and an understanding of the diversity that exists in Indonesia. This learning also strengthens attitudes of tolerance, respect for differences, and understanding the active role of each individual in national life. Thus, the national values introduced through PKn learning can form a strong attitude of nationalism in elementary school students, which in turn encourages them to play a more active role in the social, cultural, and political life of the nation. In conclusion, civics learning in elementary schools has a very vital role in building students' national and state awareness, which is very necessary in facing global challenges and building social peace in a pluralistic society. Suggestions that can be put forward are the importance of continuing to develop more interesting and relevant learning methods, such as problem-based learning, group discussions, and the use of interactive media, in order to further deepen students' understanding of national values. In addition, stronger collaboration is needed between teachers, parents, and the community in creating an educational atmosphere that supports the development of democratic attitudes and a sense of love for the homeland in students.